1998
DOI: 10.4067/s0370-41061998000500002
|View full text |Cite
|
Sign up to set email alerts
|

Arteria umbilical única y malformaciones asociadas: Experiencia en el Hospital Clínico de la Universidad de Chile

Abstract: ResumenLa are: c umbilical urrca [AUU) es una malformocicn cenfinela que debe orien'ar a la busqueca mas exhaustive de mclfcrmaciones asociadas que pueden no ser siempre evidentes, ya sea que estas se presenten en forma de sindrones a bien co r un patron desconocido. Este estudio incluye a las casos registrac'os de AUU en la Lnidad de Neonatolog'c del Hbspiral Clinico de la IHvers'dad de Chi e desde enero de 1978 hasfa abril de 1998. Observamos, como se ha reportaco en la literature, que la AUU aislada o asoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 8 publications
1
8
0
3
Order By: Relevance
“…Reported rates of associated malformations also varied between 14% [29] and 65% [19], depending on the population under study as well as on the BD classification used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported rates of associated malformations also varied between 14% [29] and 65% [19], depending on the population under study as well as on the BD classification used.…”
Section: Discussionmentioning
confidence: 99%
“…A few authors [24] have concluded that the perinatal outcomes of newborns with isolated SUA do not differ from those of infants with trivascular cords and that an adverse perinatal outcome is likely the result of the frequent coexistence of other malformations. However, the majority [1,10,14,19,32] hold that even in the absence of other malformations, mortality, low birth weight, and prematurity occur more often in newborns with SUA than in infants with trivascular cords and that the prenatal diagnosis of SUA should lead to an exhaustive monitoring of the fetus [33]. Nevertheless, it is generally agreed that the long-term prognosis is similar in infants with and without SUA.…”
Section: Perinatal Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gran importancia también tiene el hecho de el alto porcentaje de prematuros en nuestra muestra (55,4%), aún cuando otros autores no encuentran diferencias en la prematuridad entre los niños con AUU y los normales (15). Nuestros hallazgos, sin embargo, están plenamente de acuerdo con lo reportado por otros autores (7). Estos cuatro importantes hechos: asociación con anomalías estructurales mayores, anormalidades cromosómicas y aneuploidías, RCIU y prematuridad, deben obligar a realizar ecografías seriadas y extremar las medidas de control del embarazo cuando se hace el diagnóstico prenatal de AUU, por el alto riesgo de asociación con esas patologías (16).…”
Section: Discussionunclassified
“…También pueden presentarse anormalidades cromosómicas, tanto aneuploidías como trisomías 18 y 13 (7,8,9,10). La trisomía 21 se asocia con mucho menor frecuencia con AUU (4).…”
Section: Introductionunclassified